2011
DOI: 10.3379/msjmag.1104r005
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Y3-xBixFe5O12 Films for Magneto-optical Indicator Films By Metal Organic Decomposition

Abstract: Bi2.5Y0.5Fe5O12 and Bi3Fe5O12 thin films were prepared on Gd3Ga5O12 substrates using a metal organic decomposition (MOD) method as magneto-optical indicators (MOI) to visualize the distribution of magnetic flux. Their structural and magneto-optical properties were studied. The Faraday rotations of Bi2.5Y0.5Fe5O12 and Bi3Fe5O12 thin films were 15.5 m/degrees at a wavelength of 524 nm for the former and 23.0 m/degrees at 530 nm for the latter. We found that these films prepared by MOD were suitable for MOI, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…We have reported that metal-organic decomposition ( MOD) method is promising to obtain high quality garnet films with high-bismuth content because they are advantageous not only for homogeneity of the thin film, the controllability of composition, and formation over large area but also for the good productivity and stability of the MOD solution for more than several years [11][12][13][14][15][16] . In previous work, we have also reported that Nd 2 BiFe 4 GaO 12 (Bi1:NIGG) layer is effective as a buffer layer to obtain Y 2 Bi 2.5 Fe 5 O 12 , x = 2.5, on glass substrates 15 .…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that metal-organic decomposition ( MOD) method is promising to obtain high quality garnet films with high-bismuth content because they are advantageous not only for homogeneity of the thin film, the controllability of composition, and formation over large area but also for the good productivity and stability of the MOD solution for more than several years [11][12][13][14][15][16] . In previous work, we have also reported that Nd 2 BiFe 4 GaO 12 (Bi1:NIGG) layer is effective as a buffer layer to obtain Y 2 Bi 2.5 Fe 5 O 12 , x = 2.5, on glass substrates 15 .…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods to prepare the Bi:GdIG thin films such as a laser ablation [10], RF magnetron sputtering [11], liquid phase epitaxy [12], etc. Metal organic decomposition (MOD) method is a promising one to prepare magnetic garnet film, because it is a simple fabrication method which is composed of spin coating of the MOD solutions ( 12 thin films have been fabricated on (111) oriented gadolinium gallium garnet (GGG) single crystal substrates [9,10,11,12,13,14,15], and glass substrates [16]. In order to apply Bi:GdIG or Bi:YIG thin films in Si/SiO 2 based waveguide optical isolators [17,18,19] and MOSLMs [7], it is required that Bi:GdIG thin films are prepared on glass substrates or SiO 2 thin films.…”
Section: Introductionmentioning
confidence: 99%
“…A magnetic imaging technique utilizing magneto-optical (MO) imaging plates has been attracting attention, because it is more advantageous in terms of features, such as measurement time, resolution, operating temperature range, and quantitatively evaluated magnetic flux and/or currents flow (1)(2)(3)(4)(5)(6) as compared with recently developed magnetic microscopy techniques, such as magnetic force and superconducting quantum interference device (SQUID) microscopies. A Bi-substituted rare-earth iron garnet film is used as an MO imaging plate that enables the visualization of magnetic fluxes, because it exhibits a large Faraday rotation in the transmission.…”
Section: Introductionmentioning
confidence: 99%
“…We have already reported that Bi:RIG films with high Bi substitution up to x = 3 were successfully prepared on both gadolinium gallium garnet (GGG) single-crystal and glass substrates. (5)(6)(7)(8)(9)(10) We suggest that these Bi:RIG films are suitable for use as MO indicator films in magnetic imaging. In this paper, we report on Bi:RIG films prepared by MOD and MO imaging using these Bi:RIG films.…”
Section: Introductionmentioning
confidence: 99%